2016
DOI: 10.3390/su8090912
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Hydraulic Fracturing Wastewater Practices in Unconventional Shale Development: Newspaper Coverage of Stakeholder Concerns and Social License to Operate

Abstract: Abstract:In this article we review prior literature regarding the concept of social license to operate, and related concepts, including corporate social responsibility, sustainable development, stakeholder management and cumulative effects. Informed by these concepts, we search for newspaper articles published in North American provinces and states where the Barnett, Duvernay, Marcellus and Montney shale plays are located. Using these data, we tabulate coverage of stakeholder concerns related to hydraulic frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 68 publications
0
34
0
2
Order By: Relevance
“…Finally, development of the shale gas industry involves many parties [87] with different and sometimes conflicting expectations [54,88], thus, broad-based risk management efforts are required. The government should strengthen the supervision of resources, market and environmental protection to ensure that risks are minimized.…”
Section: Policy Recommendations For China's Provincial Shale Gas Indumentioning
confidence: 99%
“…Finally, development of the shale gas industry involves many parties [87] with different and sometimes conflicting expectations [54,88], thus, broad-based risk management efforts are required. The government should strengthen the supervision of resources, market and environmental protection to ensure that risks are minimized.…”
Section: Policy Recommendations For China's Provincial Shale Gas Indumentioning
confidence: 99%
“…Very importantly such opposition has become intermistic in that environmental or human rights issues, for example, are no longer framed as being a concern within a country, but have become concerns of citizens and consumers in other countries, who may take action against companies if they perceive behaviours to be wrong, and even if they have fulfilled their legal requirements [30][31]. Second, changes in in social values, that reflect the growth of political consumerism and concerns over various rights, have gone hand-in-hand with the growth of the global civil sector [3]. Third, the globalization of consumer concern over corporate activities is interrelated to the changes in communication technologies, especially the Internet, that provides various communities to voice concerns over corporate activities [6].…”
Section: The Concept Of Social License To Operatementioning
confidence: 99%
“…The term is used to suggest that a "social contract" exists between businesses, often with a project that has significant environmental change associated with it, and the various communities of interest that are or will be affected by the project. While companies are required to abide by legal permits, regulation and licence, SLO is the less tangible aspect of social acceptance, which ensures a company is not at risk or, at least, reduces the corporate risk of community conflict or protests with its projects and/or products [1][2][3]. It has been suggested that the application of SLO is meant to encapsulate particular activities, ideals and values, that allow for successful business operations [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, the viability of shale gas was regarded as either non-feasible or uneconomical due to technological limitations and low gas price. However, during the mid-2000s, the application of hydraulic fracturing and horizontal drilling in the US, coupled with the surge in gas prices, enabled the extraction of huge quantities of natural gas from shale [2]. The production of shale gas has therefore increased thirteen times between 2007 and 2016.…”
Section: Introductionmentioning
confidence: 99%